Visualidade nos contratos comunicativos em revistas de turismo: construção de imaginários para turistas - Ferrari, Cynthia Menezes Mello (2013)
The research investigates how tourism magazines, by exposing photographic images and developing communicative contracts on the perfect trip, modalised consumers-enunciatee on construction of imaginary touristic destinations so that they are figurative from that perfection. It also studies from this perspective, the strategies used by the construction of imaginary enunciators for the enjoyment of the tourist experience. The selected body is comprised of the following Magazines: Viagem e Turismo, Abril Publisher, Viaje Mais, Europa Publisher, Lonely Planet, Duetto Publisher and Viajar pelo Mundo, Emporium das Ideias Publisher, from the period 2009 to 2012. We can commence with the hypothesis that such images creates anticipation and fantasies anticipating the experiences to which they refer, functioning as recipe of the enunciator for the enunciatee. The theoretical framework is based on a set of interdisciplinary knowledge in the areas of Communication, Semiotics, Photography, Philosophy, Sociology, Anthropology and Tourism, visioning tourism phenomenon, which is the reason for our study, is permeated by the interaction of these diverse knowledge contextualized based on Beni, Krippendorf, Augé, Baumam, Sontag, Barthes, Duran, Amirou, Türcke, Semprini, Urry and Nasio. The dialogue with these researchers makes it necessary coping with critical alliance among photography, journalism and tourism itself, while producing scenes of the perfect trip. The verbal-visual analysis of magazines will adopt the model of the critical discourse analysis of Fairclough, namely the deconstruction of the text from the power relations established in the social, historical, political and economic, as well, from the semiotics of text, with Diana Barros and Landowski, supplementing it with visual semiotics, according to Jean- Marie Floch and Vicente Pietroforte. For the discussion of discursive totalities of global capitalism it will be assumed to discourse the theory of Ernesto Laclau also tourism theory Thurlow and Jaworski